Transcranial direct current stimulation to facilitate neurofunctional rehabilitation in children with autism spectrum disorder: a protocol for a randomized, sham-controlled, double-blind clinical trial - Araujo, Marcela O.; Tamplain, Priscila; Duarte, Natália A. C.; Comodo, Andréa C. M.; Ferreira, Giselle O. A.; Queiróga, Amanda; Oliveira, Claudia S.; Collange-Grecco, Luanda A. (Frontiers in Neurology, 2023)
Background: Autism spectrum disorder (ASD) can affect motor and postural control. Transcranial direct current stimulation (tDCS) is a tool capable of favoring learning and motor performance by facilitating cortical excitability. If administered during motor training, tDCS is capable of increasing the effect size of training. The aim of the proposed study is to determine whether anodal tDCS over the primary motor cortex and cerebellum can enhance the effects of gait training and postural control on motor skills, mobility, functional balance, cortical excitability, cognitive aspects and behavioral aspects in children with ASD. Our hypothesis is the active tDCS combined with motor training will enhance the performance of the participants in comparison to sham tDCS. Methods and design: A randomized, sham-controlled, double-blind clinical trial will be conducted involving 30 children with ASD. The participants will be randomized to three groups: experimental group 1 (anodal tDCS over the primary motor cortex combined with motor training), experimental group 2 (anodal tDCS over the cerebellum combined with motor training) and control group (sham tDCS combined with motor training). The intervention will consist of five sessions per week for two consecutive weeks (total of 10 sessions). Active (1 mA) or sham tDCS will be administered during 20 minutes of treadmill training and postural control training (balance activities). The participants will be assessed before as well as one, four and eight weeks after the interventions. The primary outcome will be gross and fine motor skills. The secondary outcomes will be mobility, functional balance, motor cortical excitability (evoked motor potential), cognitive aspects and behavioral aspects. Discussion: Although abnormalities in gait and balance are not primary characteristics of ASD, such abnormalities compromise independence and global functioning during the execution of routine activities of childhood. If demonstrated that anodal tDCS administered over areas of the brain involved in motor control, such as the primary motor cortex and cerebellum, can enhance the effects of gait and balance training in only ten sessions in two consecutive weeks, the clinical applicability of this stimulation modality will be expanded as well as more scientifically founded. Trial Registration: February 16, 2023 (https://ensaiosclinicos.gov.br/rg/RBR-3bskhwf)